Is The CIPP Model More Effective in Evaluating Counseling Services in The Merdeka Curriculum? - Setiawan, Muhammad Andri; Sari, Nina Permata; Makaria, Eklys Cheseda; Novitawati, Novitawati; Rizani, Salwaa Alma; Refli, Muhammad (Vidya Karya, 2024)
This study aimed to evaluate the effectiveness of the CIPP (Context, Input, Process, Product) evaluation model in assessing Guidance and Counseling (GC) services within the Merdeka Curriculum at Vocational High School 3 and Vocational High School 4 in Banjarmasin. A quantitative method with a comparative approach was employed. Data were collected using questionnaires completed by students from both schools, and the data analysis involved a t-test to examine differences between the schools. The findings revealed that Vocational High School 4 achieved higher evaluation scores across all CIPP components compared to Vocational High School 3 Banjarmasin. Significant differences were observed in the context, input, process, and product components, with p-values <0.05. These results indicated that GC services at Vocational High School 4 Banjarmasin were more effective in implementing the Merdeka Curriculum. The study concluded that the CIPP model is an effective evaluation tool for identifying the strengths and weaknesses of GC service programs. The implications of this research suggest that improvements in the input and process components could enhance the quality of GC services at Vocational High School 3 Banjarmasin.